PkM Masyarakat Sehat dan Berkarakter di Kampung Sidotopo Kedungsari Magelang - Galih Dwi Pradipta; Osa Maliki; Rahmat Sudrajat; Supriyono Supriyono (Universitas PGRI Semarang, 2021)
Sidotopo Village, Kedungsari Village, North Magelang, Magelang City is a densely populated area and a wide variety of people live in the area. The characteristics of the people who live in the area are diverse in their occupations and education, some residents do not receive formal education and some residents also work odd jobs, ranging from garbage collectors, food sellers and others. Awareness of a clean, healthy and characterized life seems to be lacking in local residents, as evidenced by the fact that there are still people who throw garbage in the river, do not recognize the importance of exercise and food intake with good nutrition, and lack of understanding of national character in terms of defending the country. Mentoring/socialization about clean, healthy and character living is a solution in forming a healthy and characterized society. The assistance provided to the community is an understanding of clean living, an understanding of the importance of maintaining health by exercising, and the importance of having a strong national character. So there is great hope to add insight to the community to be able to live healthy and have character in Sidotopo Village. Keywords: Clean Living, Healthy Exercise, Love for the Motherland.Kampung Sidotopo Kelurahan Kedungsari Magelang Utara Kota Magelang merupakan daerah yang padat penduduk dan beraneka ragam masyarakat yang tinggal di daerah tersebut. Karakteristik masyarakat yang tinggal di daerah tersebut beraneka ragam pekerjaan dan pendidikanya, beberapa penduduk ada yang tidak mengenyam pendidikan secara formal dan beberapa penduduk juga ada yang bekerja serabutan, mulai dari pengepul rongsok, penjual makanan dan lain-lain. Kesadaran akan hidup bersih, sehat dan berkarakter nampaknya kurang dirasakan oleh penduduk sekitar, terbukti dengan masih adanya masyarakat yang membuang sampah di kali, tidak mengenalnya pentingnya olahraga dan asupan makanan dengan gizi yang baik, serta kurangnya pemahaman tentang karakter kebangsaan dalam hal bela negara. Pendampingan/sosialisasi tentang hidup bersih, sehat dan berkarakter merupakan solusi dalam membentuk masyarakat sehat dan berkarakter. Pendampingan yangh diberikan kepada masyarakat yaitu pemahaman akan hidup bersih, pemahaman pentingnya menjaga kesehatan dengan berolahraga, serta pentingnya memiliki karakter kebangsaan yang kuat. Sehingga besar harapan menambah wawasan masyarakat untuk dapat hidup sehat dan berkarakter di kampung sidotopo. Kata kunci: Hidup Bersih, Sehat Berolahraga, Cinta Tanah Air.